(E)-2-Methyl-6-{[(5-methylpyridin-2-yl)imino]methyl}phenol - Md. Azharul Arafath; Farook Adam; Mohd. R. Razali (IUCrData, 2017)
In the title compound, C14H14N2O, the dihedral angle between the aromatic rings is 5.54 (9)°. The conformation is reinforced by an intramolecular O—H...N hydrogen bond, which closes an S(6) ring. The pyridine N atom and methyl group lie to opposite sides of the molecule. In the crystal, the molecules are linked into a zigzag chain propagating in [0-11] by weak C—H...O hydrogen bonds.